Maternal and neonatal outcomes in pregnancies complicated by maternal obesity - Menon, Sudha; K., Sivaprasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal obesity imparts elevated maternal and neo natal adverse outcomes. Aim of the study was to evaluate and analyse the maternal and neonatal outcomes in obese mothers. Methods: This was a prospective case control study in a tertiary care high risk referral center. Antenatal women with first trimester Body mass index (BMI) of more than 30 Kg/m2 constituted the cases and those antenatal women with BMI <25 Kg/m2 formed the controls. Results: Mean age was slightly more (28.6±4.3 years vs 26.3±3.6 years: P<0.0001) in the obese group. Obese women were significantly more likely to have of gestational diabetes (OR 5.2, 95% CI 3.2-8.7 P<0.00001), gestational hypertension (Or 3.5, 95% CI 2.1-5.9 P<0.0001) , induction of labour (OR 2.5, 95% CI 1.8-3.6 P<0.0001), failed induction of labour (OR 2.4, 95% CI 1.3-4.2 P=0.003), Preeclampsia (OR 2.8, 95% CI 1.6-4.9 P=0.0002), Caesarian section (Or 4.0, 95% CI 2.9-5.9 P<0.0001) and Postpartum hemorrhage (OR 4.0,95% CI 1.1-14.3 P=0.034), prolonged hospital stay (OR 12.8, 95% CI 7.7-21.1 P<0.0001) and adverse neonatal outcomes such as low(<7) Apgar (OR 3.2, 95% CI 1.1-10.0 P=0.03), Large for gestational age babies (OR 3.1, 95% Cl 2.1-4.5 P<0.0001) and transfer to new born nursery (OR 3.4, 95% CI 2.3 -5.2 P<0.0001). Conclusions: Maternal obesity in pregnancy is high risk and has many adverse maternal and neonatal outcomes warranting specialized antenatal, intranatal and post-natal care.